2013
DOI: 10.1002/asia.201300760
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Amines with 8‐MethylthioBODIPY: Dramatic Optical and Laser Response to Amine Substitution

Abstract: A thorough study of the photophysical and laser properties of 8-aminoboron dipyrromethene dyes was undertaken to determine the role of amine substitution and spatial disposition on the properties of the dyes. It was found that the fluorescent and laser response varied significantly. Although primary amines give rise to highly fluorescent products at the blue edge of the visible region, secondary amines yield nonfluorescent analogues in polar media. The crystal structures of two analogues are reported and descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 57 publications
1
38
0
1
Order By: Relevance
“…100 nm) when compared with related 8‐(methylthio)BODIPY 17 , in agreement with the Hammett σ ‐parameter of the groups located at position 8 ( σ p + = −1.81 for NHMe and σ p + = −0.60 for SMe) (76). This effect is mainly attributed to the high contribution of a hemicyanine‐like BODIPY structure in the case of the aminated derivatives (78‐80). Indeed, the higher the electron‐donor capacity of the amine is, the higher the blueshift is, as it is shown by BODIPY 14 with a methyl group ( σ p + = −0.31) involved in the 8‐(methylamino) moiety, in comparison with a propargyl one (with lower electron‐donor strength; σ p + = +0.18) involved in the 8‐(propargylamino) group of BODIPY 15 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…100 nm) when compared with related 8‐(methylthio)BODIPY 17 , in agreement with the Hammett σ ‐parameter of the groups located at position 8 ( σ p + = −1.81 for NHMe and σ p + = −0.60 for SMe) (76). This effect is mainly attributed to the high contribution of a hemicyanine‐like BODIPY structure in the case of the aminated derivatives (78‐80). Indeed, the higher the electron‐donor capacity of the amine is, the higher the blueshift is, as it is shown by BODIPY 14 with a methyl group ( σ p + = −0.31) involved in the 8‐(methylamino) moiety, in comparison with a propargyl one (with lower electron‐donor strength; σ p + = +0.18) involved in the 8‐(propargylamino) group of BODIPY 15 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All these molecules are selected from reliable spectroscopic and photophysical studies reported by experimental researchers. 22,24,26,27,29,30,34,35,37,40,45,50,51,59,[62][63][64][65]67 We present the identities of X 1 through X 8 , λ abs , and λ fl of these molecules (compounds 1 through 100) in Tables S1 and S2, their E abs , E fl , and | µ fl | in Tables S3 and S4, and their k fl , k nr , and Φ fl in Tables S5 and S6.…”
Section: Photophysics Of Bodipymentioning
confidence: 99%
“…[127][128][129][130] For BODIPY we follow the experimental evidence that only one of the S 1 → S 0 and S 1 → S 2 (or L a → L b ) ICs is fast enough to be observed, being at least two orders of magnitude faster than any other nonradiative channel. 9,12, 22,24,26,27,29,30,35,42,46,47,50,51,62,64,66,67,[100][101][102]110,152,163 As a result,…”
Section: Quantum Yieldmentioning
confidence: 99%
See 2 more Smart Citations